Chemoinformatics and machine learning techniques to identify novel inhibitors of the lemur tyrosine kinase-3 receptor involved in breast cancer - Alrumaihi, Faris (Frontiers in Molecular Biosciences, 2024)
Breast cancer is still the largest cause of cancer death in women, and around 70% of primary breast cancer patients are Estrogen receptor (ER) positive, which is the most frequent kind of breast cancer. The lemur tyrosine kinase-3 (LMTK3) receptor has been linked to estrogen responsiveness in breast cancer. However, the function of LMTK3 in reaction to chemotherapy that is cytotoxic has yet to be studied. Breast cancer therapies research remains tricky due to a paucity of structural investigations on LMTK3. We performed structural investigations on LMTK3 using molecular docking and molecular dynamics (MD) simulations of the LMTK3 in complex with top 3 inhibitor molecules along with control inhibitor. Analysis reveals top three compounds show best binding affinities during docking simulations. Hydrogen bonds interactive analysis inferred hot spot residues Tyr163, Asn138, Asp133, Tyr56, Glu52, Ser132, Asp313, Asp151. Some other residues in the 5-angstrom region determined strong alky bonds and conventional hydrogen bonds linkages. Furthermore, protein dynamics analysis revealed significant modifications among the top complexes and control system. There was a transition from a loop to a -helix conformation in the protein-top1 complex and in contrast, complex top2 and top3 observed the formation of a stabilizing -sheet in the C-chain, which limited significant mobility and increased complex stability. Significant structural alterations were observed in the protein-top complexes, including a shorter helix region and the creation of some loop region in comparison to the control system.Interestingly, binding free energies including MMGB/PBSA Waterswap analysis estimation reveals that top1 complex system was more stable as compared to other systems especially in comparison to control inhibitor complex system. These results suggest a plausible mode of action for the novel inhibitors. Therefore, this current investigation contributes to understanding the mechanism of action, serving as a basis for future experimental studies.